Pemanfaatan Hasil AUM PTSDL untuk Pelayanan Bimbingan dan Konseling - Utomo, Dian Purbo; Prayitno, Prayitno; Effendi, Z Mawardi (Konselor, 2017)
This research purposed to describe the results of AUM PTSDL and its use by Guidance and Counseling Teacher or Counselor for Guidance and Counseling services to students. This research used descriptive method with qualitative and quantitative approach. The instruments of research used AUM PTSDL Format 2, The format of BMB3 and guideline for interview. The results of research are analyzed statistically and narrative. This research shows that AUM PTSDL results of Senior High School students in Padang who became samples in form quality score of learning activities still very low or less is average 36.30% from ideal score, and also their learning problems pretty much is average 28,14% from number of learning problems that may exist. Response dynamics of BMB3 student to data of AUM PTSDL results are quite positive, means that students are aware of their flaws and eager to fix it. Guidance and Counseling Teacher or Counselor welcomes positively to awareness and enthusiasm of students accompanied prepare themselves in use AUM PTSDL and utilization results to improve the quality of their learning activities by Guidance and Counseling services, which organized through various types of services and their supporting activities in specific format. The school’s leadership have role in facilitating the implementation of Guidance and Counseling services and supports Guidance and Counseling Teacher or Counselor performance at school.